2001
DOI: 10.1103/physrevb.64.064506
|View full text |Cite
|
Sign up to set email alerts
|

Electronic structure ofCeRhIn5:de Haas–van Alphen and energy band calculations

Abstract: The de Haas -van Alphen effect and energy band calculations are used to study angular dependent extremal areas and effective masses of the Fermi surface of the highly correlated antiferromagnetic material CeRhIn5. The agreement between experiment and theory is reasonable for the areas measured with the field applied along the (100) axis of the tetragonal structure, but disagree in size for the areas observed for the field applied along the (001) axis where the antiferromagnetic spin alignment is occurring. Det… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

14
53
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(67 citation statements)
references
References 11 publications
14
53
0
Order By: Relevance
“…55,89) With increasing pressure, the dHvA amplitude is strongly reduced, but the dHvA frequencies for main cylindrical Fermi surfaces are unchanged up to 2.1 GPa, which is above P Ã ¼ 1:6 GPa where superconductivity sets in. Figure 23 shows the pressure dependence of the cyclotron mass, which was determined at H ¼ 12 T. 82) The cyclotron mass increases steeply above 1.6 GPa.…”
Section: )mentioning
confidence: 99%
“…55,89) With increasing pressure, the dHvA amplitude is strongly reduced, but the dHvA frequencies for main cylindrical Fermi surfaces are unchanged up to 2.1 GPa, which is above P Ã ¼ 1:6 GPa where superconductivity sets in. Figure 23 shows the pressure dependence of the cyclotron mass, which was determined at H ¼ 12 T. 82) The cyclotron mass increases steeply above 1.6 GPa.…”
Section: )mentioning
confidence: 99%
“…The recent Muon knight shift measurements also found that the magnetic field dependence of the reduction of the muon knight shift is not in proportion to √ H, which is roughly explained by the Fermi liquid relation and is inconsistent with simple expectation for a d-wave superconductors 29 . These facts likely reflect the multiband nature of superconductivity in CeCoIn 5 , similar to the story of Fe-based superconductors 16,17 .On the other hand, de Hass-van Alphen (dHvA) experiments in CeCoIn 5 clearly indicate the FS is three dimensional (3D) [30][31][32] . If quasi-2D FS (a large FS denoted as β-band in the dHvA experiments) is strictly cylindrical along the k z direction, the hot lines would be parallel to k z .…”
mentioning
confidence: 87%
“…1. Note that band E k− reproduces the above FS and is denoted as the β-band in the de Hass van Alphen experiments [30][31][32] . While band E k+ remains above the Fermi energy, and thus has no contribution to the FS topological structure.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Previous dHvA studies of CeRhIn 5 (x = 0) [5,4,6] and CeCoIn 5 (x = 1) [7] have established the Fermi surface of both compounds to have a common geometry consisting of: (1) a heavy quasi-2D cylindrical sheet giving rise to orbits labeled α i , (2) a heavy and more complex quasi-2D sheet with orbits β i , and (3) several small, light pockets with corresponding low-frequency orbits [7]. Band structure calculations [8] compare well with these observations if the Ce 4f electrons are treated as localized in CeRhIn 5 and itinerant in CeCoIn 5 , a picture further supported by comparisons to the non-f -electron analogue LaRhIn 5 [5,9].…”
Section: Methodsmentioning
confidence: 99%